Perlindungan Hukum Terhadap Pengguna Jasa Telekomunikasi dalam Pelanggaran Data Pribadi Melalui sms Broadcast - Aziz Muhaimin; Ni Made Jaya Senastri; Ni Made Sukaryati Karma (Jurnal Preferensi Hukum, 2021)
11 the progress of the modern era today where the development of internet technology,SMS and social media becomethe main thing in every need of society in socializing and conductingpromotionsat an affordablecost andfast in reaching consumers,so that indirectlythe exchange ofpersonaldata informationthat is not known by service users who are often misused by irresponsiblepeople. Which in practiceis to use SMSBroadcast which is one method of sending messagesto many numbers from one source with the same message with one number to another consumer number. From the statement, there are 2 problems, namely How to set the law of telecommunicationservice users in the field of advertising and How to protectthe lawfor consumers with the existence ofpersonaldata breaches through SMS Broadcast.The method to be used is a method of normative legal research. The conclusion outlines that Article I of the Consumer Protection Law Serves as the legal basis for the protection of telecommunication service users, while in Article 26 of the /TE Law is used as the legal basis for the use of personal data, which in this case is SMS Broadcast